Elaborate interface design of SnS2/SnO2@C/rGO nanocomposite as a high-performance anode for lithium-ion batteries. (10th February 2022) - Jin, Shuangling; Gu, Feijiao; Wang, Jitong; Ma, Xia; Qian, Chenliang; Lan, Yaxin; Han, Qi; Li, Junqiang; Wang, Xiaorui; Zhang, Rui; Qiao, Wenming; Ling, Licheng; et al.
Highlights: Tightly contacted SnS2 /SnO2 heterostructure is formed by in-situ oxidation of SnS2 . The amorphous carbon can strongly anchor SnS2 /SnO2 nanoparticles on rGO sheets. N and S heteroatoms are co-doped into rGO by using thiourea as N and S sources. The reaction reversibility and kinetics are enhanced at SnS2 /SnO2 heterojunctions. The carbon and rGO guarantee the electrical connection and structural stability. Abstract: The practical application of Sn-based anode materials is limited by their low electrical conductivity and large volume expansion during cycling. To overcome these challenges, a novel SnS2 /SnO2 @C/rGO nanocomposite is synthesized by in-situ H2 O2 oxidation of SnS2 @C/rGO that is prepared via a hydrothermal reaction using SnCl2, thiourea, L-ascorbic acid and GO as the reactants. Tightly contacted SnS2 /SnO2 heterostructured nanoparticles are encapsulated by the amorphous carbon derived from L-ascorbic acid, which are further firmly anchored on the rGO sheets through the chemical interactions between the hydroxyl groups of L-ascorbic acid and hydroxyl/carbonyl groups of rGO. The amorphous carbon layer can act as a spacer to prevent the stacking of rGO sheets to retain the ion transport pathway. Meanwhile, the N and S heteroatoms are co-doped into the rGO sheets by using thiourea as N and S sources, which can enhance the electrical conductivity and provide more active sites for Li + insertion/extraction. The obtained nanocomposite exhibits a specific capacity of 689 mA h g −1 after 300 cycles at a current density of 0.1 C (1 C = 783 mA g −1 ) and a moderate capacity of 619 mA h g −1 up to 500 cycles at a large current rate of 0.5 C. Graphical abstract: Image, graphical abstract